Protein Analysis-on-Chip Systems in Foodomics - Nazzaro, Filomena (MDPI, 2012)
Protein compositional data can address nutritional, packaging, origin/authenticity, processing history, safety and other quality questions. Such data has been time-consuming and expensive to generate until recently but “protein analysis on a chip” systems are now available that can analyze a complex food sample in a few minutes and do not require great protein analytical expertise. We review some of the main new approaches with examples of their application and discuss their advantages and disadvantages.